The lost art of listening - Nichols, Michael P. 1945- (Guilford Press, 1995)
We never outgrow our need to connect with others--to feel as though we are heard and understood. That is why a sympathetic ear is such a powerful force in human relationships--and why the failure to be heard is so painful. But why do we often feel cut off when speaking to the people closest to us, family members, friends, or colleagues? What is it that keeps so many of us from really listening? Psychologist Michael P. Nichols answers these questions and more in this ground-breaking exploration of why people don't hear one another. His book, an engaging guide to the secrets of listening and being listened to, is filled with examples that clearly demonstrate easy-to-learn techniques for becoming a better listener. He also illustrates how empathic listening enables us to break through misunderstandings and conflict and to transform our personal and professional relationships.--From publisher description.
Keywords: Communication interpersonnelle; Relations humaines; Écoute (Psychologie); Communication; Interpersonal Relations; Interpersonal communication; Interpersonal relations; Listening; Hören; Kommunikation; Zwischenmenschliche Beziehung; Zuhören; Aufmerksamkeit